2012
DOI: 10.5961/jhes.2012.050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality traits of high school teachers on their teacher qualifications

Abstract: GİRİŞÖğre m süreci büyük oranda öğrencilerle öğretmenlerin etkileşimlerine dayanır. Bu etkileşimin merkezinde öğretmen ve öğrencilerin kişilikleri vardır. Jones (1989) öğre min "kişisel" faktörlere dayalı bir etkileşim olduğundan dolayı, gerçekten etkili öğre msel çevrenin oluşturulması için gereken "kişisel" faktörlerin anlaşılması gerek ğini iddia etmiş r. Bu öğre m süreci öğretmen ve öğrenciler arasındaki etkileşime dahil olan kişilik özellikleriyle hem kolaylaş rılabilir hem de güçleş rilebilir.Öğretmen ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Personality types of the educator do infer preferred teaching methods and styles as well as dimensions of teachers' professional performance (Curtis & Cheng, 2001;Ionescu, 2013). Earlier research, analyzing the association between personality traits and effectiveness in teaching highlighted that extraversion, agreeableness, and conscientiousness traits of personality have a positive correlation with effectiveness of teaching (Kim & MacCann, 2018;Kim et al, 2018;Klassen et al, 2017) whereas traits of neuroticism and openness do not have indicative relationship to teachers' effectiveness (Kalafat, 2012;Othman, 2009). Assertiveness correlates with several professional performance dimensions and extraversion was an affirmative characteristic of teachers (Clayson & Sheffet, 2006;Emmerich et al, 2006;Ionescu, 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Personality types of the educator do infer preferred teaching methods and styles as well as dimensions of teachers' professional performance (Curtis & Cheng, 2001;Ionescu, 2013). Earlier research, analyzing the association between personality traits and effectiveness in teaching highlighted that extraversion, agreeableness, and conscientiousness traits of personality have a positive correlation with effectiveness of teaching (Kim & MacCann, 2018;Kim et al, 2018;Klassen et al, 2017) whereas traits of neuroticism and openness do not have indicative relationship to teachers' effectiveness (Kalafat, 2012;Othman, 2009). Assertiveness correlates with several professional performance dimensions and extraversion was an affirmative characteristic of teachers (Clayson & Sheffet, 2006;Emmerich et al, 2006;Ionescu, 2013).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Some researchers state that all goodness-of-fit measures are a function of the chi-square and the degrees of freedom (Hox, 2021). Thus, the X^2/df ratio is regarded as the adequacy criterion of the model (Cihangir Çankaya, 2009;Kalafat, 2012). Browne andCudeck (1993), andSörbom (1993) suggest that RMSEA < 0.05 indicates a close fit (Xia & Yang, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A study on the relation between personality traits of prospective teachers at teacher education centers revealed that the dominant trait among the teachers is openness that had more relevance than other traits (Arif, et al, 2012). More specifically, Kalafat (2012) suggested a model to investigate the effects of high school teachers' personality on their perceived teaching competencies. He found out that openness and conscientiousness have a positive effect on teaching competencies; however, neuroticism has a negative effect on them.…”
Section: Literature Reviewmentioning
confidence: 99%